Limb salvage surgery for giant cell tumours around knee joint: a single institute experience - Prabha, Amritha; Shah, Urvish K.; Ganesh, M. S.; Seenappa, Hiranya K. (International Journal of Research in Orthopaedics, 2021)
Background: Giant cell tumours (GCTs) of bone are benign but locally aggressive tumours. The surgical treatment of GCTs in the around knee joint mainly includes curettage and bone grafting, extended curettage and cement filling, segmental resection and modular endo prosthesis reconstruction. Methods: Retrospective analysis of the presentation, the functional outcome following modular endoprosthetic reconstruction, prosthetic survival and the recurrence rate in 17 patients with Campanacci grade 3 GCTs involving distal femur and proximal tibia, who underwent segmental resection and modular endoprosthesis reconstruction in a single centre from 2015 to 2018. The surgery was performed according to the general principles of limb salvage surgery and modular segmental replacement was used. All stems were cemented in place. Isometric exercises and mobilization with crutches were started on 2nd postoperative day. Knee joint bending was started for proximal tibia patients after 2 to 3 weeks. Functional outcome was scored by musculoskeletal tumour society scoring (MSTS). Immediate post-operative complication like delayed wound healing, flap necrosis, wound infection, foot drop, leg length discrepancies were evaluated. Results: The average MSTS functional score was 78%.3 year prosthetic survival was 100%. None of the patients had recurrence. One patient had left lower lobe metastasis for which wedge resection was done. Conclusions: Segmental resection and endoprosthetic replacement has good functional outcome in patients with tumours around the knee joint. As GCTs are tumours with less chance of local and distant metastasis after complete excision, endoprosthetic prosthesis is a good treatment option after complete excision.